Elder Abuse - Starr, Deia; Wilken, Carolyn (My University, 1994)
This publication is designed to educate participants about the growing problem of elder abuse and to inform them of the possible risk factors associated with abusers and abusees.
MF1160_1994_08
Keywords: MF1160; Health and Safety; Home and Family; MF